An annotated check-list of lophogastrids (Crustacea: Lophogastrida) from the seas of the Iberian Peninsula - Vicente, Carlos San (Zootaxa, 2016)
The zoogeographic distribution of lophogastrid species occurring in the diverse seas of the Iberian Peninsula and neighbouring areas is analysed. For each species, data on general distribution, bathymetric ranges, habitat and localities reported on published data are provided. A total of 16 lophogastrids species belonging to 6 genera have been recorded, representing the 30% of all known world extant species and the 67% of genera. Two of them are common to the Atlantic and the Mediterranean. All known Iberian species are present in the Macaronesian region, 43.8% in the North-western Atlantic and 12.5% in the western Mediterranean. Lophogastrid distributions suggest the existence of an evolution and distribution centre of the group located around the Macaronesian Islands.